2015
DOI: 10.1007/s11999-014-3780-x
|View full text |Cite
|
Sign up to set email alerts
|

The Otto Aufranc Award: Modifiable versus Nonmodifiable Risk Factors for Infection After Hip Arthroplasty

Abstract: Background Periprosthetic joint infections (PJIs) are associated with increased morbidity and cost. It would be important to identify any modifiable patient-and surgicalrelated factors that could be modified before surgery to decrease the risk of PJI. Questions/purposes We sought to identify and quantify the magnitude of modifiable risk factors for deep PJIs after primary hip arthroplasty. Methods A series of 3672 primary and 406 revision hip arthroplasties performed at a single specialty hospital over a 3-yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
78
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 159 publications
(83 citation statements)
references
References 20 publications
1
78
0
2
Order By: Relevance
“…Readmission rate in particular has become a centerpiece for performance as hospitals can lose on upfront reimbursement due to Medicare's Readmission Reduction Program, face risk-based losses in pay-for-performance models, or receive no reimbursement at all for readmissions related to "never" or "zero-tolerance" events [7,11]. At the same time, several primary TJA bundled payment programs have credited reduction of inpatient LOS as a major lever for creating cost savings relative to baseline [9,12,13].…”
Section: Discussionmentioning
confidence: 99%
“…Readmission rate in particular has become a centerpiece for performance as hospitals can lose on upfront reimbursement due to Medicare's Readmission Reduction Program, face risk-based losses in pay-for-performance models, or receive no reimbursement at all for readmissions related to "never" or "zero-tolerance" events [7,11]. At the same time, several primary TJA bundled payment programs have credited reduction of inpatient LOS as a major lever for creating cost savings relative to baseline [9,12,13].…”
Section: Discussionmentioning
confidence: 99%
“…Alcohol cessation or a reduction in consumption four weeks prior to surgery is effective in reducing the risk of developing postoperative complications. [2, 25]…”
Section: Before the Day Of Surgerymentioning
confidence: 99%
“…This includes proper timing of surgery, cessation of DMARDs, proper skin preparation, and antibiotic prophylaxis. The cessation of DMARDS should be performed in consultation with a rheumatologist, which can be arranged based on the specific medication, the individual patient, and the half-life of the particular medication [2]. Although there is no clear evidence, routine use of antibiotic-laden cement for fixation in IJD patients may be justified.…”
Section: Before the Day Of Surgerymentioning
confidence: 99%
See 1 more Smart Citation
“…[41][42][43] Nasal carriers have increased rates of skin colonization, which is important to note because the skin is directly exposed to the surgical field at incision. Maoz et al 44 found that S aureus colonization was a risk factor for infection following THA; compared with patients without preoperative colonization, patients colonized with the bacteria had a 2.36 relative risk for infection. In patients with multiple risk factors, S aureus colonization can further magnify the risk of infection ( Table 2).…”
Section: Staphylococcus Aureus Carrier Screening and Decolonizationmentioning
confidence: 99%